Prevalence of Aerobic Bacteria in the Hands of School-Going Children of Rural Areas of Eastern Part of Nepal - Ghimire, Gyanendra; Rajbhandari, Sanjeev Das; Pandeya, Deependra Raj; Singh, Yankpam Ibotomba; Adhikari, Binita; Pradhan, Manoj (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: The aim of this study was to find out the prevalence of bacteria in hands of school going children in a rural area of eastern part of Nepal. Contaminated hands play a major role in faeco-oral transmission of diseases. The students can expose themselves to infection if they do not properly wash their hands before taking food. Methods: The study was done in a remote school of eastern part of Nepal in 2013. A prospective study was done on 200 school children of age group 10 years to 15 years. Swab samples collected from all the children were transported to the laboratory within one to two hours of its collection. The samples were kept in nutrient broth for overnight incubation. They were then sub-cultured aerobically at 37°C on 5% defibrinated sheep blood agar and MacConkey agar plates for 24-48 hrs. Then the plates were examined to quantify the organisms present according to Clinical Laboratory Standard Institute (CLSI) guidelines. Results: Out of 200 dominant hand swabs of school children of age group 10 years to 15 years, 52 children (26.0%) were harboring pathogenic bacteria in their hands. The major aerobic pathogenic bacteria in hands were i.e. Staphylococcus aureus, Streptococcus spp, Enterococci spp, Escherichia coli, Klebsiellaspp, Acinetobactersppand Pseudomonas aeruginosa. In most of the hands normal flora like Diphtheroids spp, Coagulase negative Staphylococci (CONS), Micrococci spp and some yeast were found. Conclusion: The finding of the study concludes that there is high incidence of aerobic bacterial flora in the hands of school going children of eastern part of Nepal. The incidence of infection was due to lack of proper hand washing before meal. The school should be told to keep soaps in the toilets for hand washing and conduct continue health education about proper hand washing and maintain cleanliness both in the schools and at the community level.